2015
DOI: 10.4278/ajhp.131120-quan-595
|View full text |Cite
|
Sign up to set email alerts
|

Do Adolescent Smokers Use E-Cigarettes to Help Them Quit? The Sociodemographic Correlates and Cessation Motivations of U.S. Adolescent E-Cigarette Use

Abstract: E-cigarette use is more common among certain adolescent subgroups than others and does not appear to be part of a cessation regimen among conventional cigarette smokers wishing to quit. More regulatory and prevention efforts are needed, especially for certain adolescent subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 18 publications
4
33
0
3
Order By: Relevance
“…10 In addition, high levels of dual use of ENDS and conventional cigarettes have been noted in both adults 13,14 and youth. 6,9,10,12,15 Among youth, self-reported e-cigarette use was also associated with higher odds of ever or current conventional cigarette smoking. 15 Compared with nonusers, youth who used e-cigarettes perceived them as healthier than cigarettes 10 ; however, youth using e-cigarettes were less likely to achieve abstinence from conventional cigarettes.…”
Section: Epidemiology Of Youth Ends Usementioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, high levels of dual use of ENDS and conventional cigarettes have been noted in both adults 13,14 and youth. 6,9,10,12,15 Among youth, self-reported e-cigarette use was also associated with higher odds of ever or current conventional cigarette smoking. 15 Compared with nonusers, youth who used e-cigarettes perceived them as healthier than cigarettes 10 ; however, youth using e-cigarettes were less likely to achieve abstinence from conventional cigarettes.…”
Section: Epidemiology Of Youth Ends Usementioning
confidence: 99%
“…8,11 ENDS use has been documented as highest among male subjects, non-Hispanic white youth, and Hispanic youth. 8,12 A 2013 survey of high school students found that e-cigarette-only users had fewer social and behavioral risk factors than conventional cigarette users, raising concern that ENDS are attracting youth who may not otherwise have used tobacco products. 10 In addition, high levels of dual use of ENDS and conventional cigarettes have been noted in both adults 13,14 and youth.…”
Section: Epidemiology Of Youth Ends Usementioning
confidence: 99%
“…De motivatie om te stoppen met roken lijkt voor jongeren minder vaak een reden om de e-sigaret te gebruiken, dan voor volwassenen (Dautzenberg et al 2013;Lippert 2014;Sutfin et al 2013). Zo toont een grootschalig onderzoek in de Verenigde Staten geen samenhang tussen enerzijds het verlangen om te stoppen met roken en recente stoppogingen en anderzijds e-sigaretgebruik onder rokende middelbare scholieren (Lippert 2014).…”
Section: Inleidingunclassified
“…Zo toont een grootschalig onderzoek in de Verenigde Staten geen samenhang tussen enerzijds het verlangen om te stoppen met roken en recente stoppogingen en anderzijds e-sigaretgebruik onder rokende middelbare scholieren (Lippert 2014). Nieuwsgierigheid en experimenteergedrag lijken voor jongeren belangrijke alternatieve motivaties om een e-sigaret te gebruiken (Dautzenberg et al 2013;Goniewicz en Zielinska-Danch 2012).…”
Section: Inleidingunclassified
“…Indeed, a number of recent studies have shown that the use of e-cigarettes does not clearly relate to interest in smoking cessation (Kinnunen et al, 2014;Lippert, 2014;Tucker at al., 2014) and that the most common reason for e-cigarette use was the capacity for use in smoke-free zones (Adkison et al, 2013;Tucker et al, 2014). For example, a study of homeless youth reported that not having to go outside to smoke was the most common reason for using ECs (38%), whilst it was less common to report using e-cigarettes to quit smoking (17-18%;Tucker et al, 2014).…”
Section: Page 12 Of 26mentioning
confidence: 99%